Malaysian and Libyan Perspectives on Single-Use Plastic’s Environmental Impact During the Pandemic COVID-19: A Pilot Study - Ali Zreba , Kamal Yousef; Tengku Izhar, Tengku Nuraiti; Mohd Saad, Farah Naemah; Zakarya, Irnis Azura; A. Hwidi, Rajeb Salem (International Journal of Integrated Engineering, 2023)
Plastics have become a significant threat to natural ecosystems as well as human health. The use and consumption of plastics improves our quality of life significantly, but it is critical to transition to more sustainable alternatives. Thus, the current study proposes an investigation into the impact of single use plastic products during pandemic on the impact to the environment from the Malaysian and Libyan perspective. A pilot study was conducted to examine the strength of the questionnaire in collecting on the environmental impacts of single use plastic during COVID-19 pandemic distributed across two countries (Libya and Malaysia). SPSS was used to test the questionnaires’ strength with 40 participants, 20 in each nation. The reliability test results with Cronbach’s Alpha predicted values of 0.7-0.86 and actual data Alpha values 0.87-0.93, normal test of variance inflation factor ranging between 1 and 5, skewness and kurtosis values of -1.343 to -0.076 and 5.312 to -0.024 respectively confirmed the strength of the questionnaires as benchmarked in the literature. Further, the participants’ responses to the quality of the questionnaire in determining the single use plastic impact to environmental have clearly revealed the strength and applicability of this questionnaire for wider data collections.